The Need for a State System of Scientific and Technical Support for Criminal Procedure - A. F. Volynskii (Теория и практика судебной экспертизы)
The article consistently analyzes the features of forensic expert activities’ emergence and development. It also shows the substantive features of these activities, the reasons, and circumstances of the manifestation of interdepartmental contradictions in the approaches to their organization. The author concludes that it is necessary to form a nationwide (supra-departmental) system of scientific and technical support for criminal proceedings, including forensic expert activities and computer forensics.